Sphinx or warrior? A small, bronze head from Pyla-Kokkinokremos, Cyprus - Driessen , Jan; Gaignerot-Driessen , Florence; Hermon , Sorin (Journal of Greek Archaeology, 2024)
The coastal hill-site of Pyla-Kokkinokremos, located in the east part of Larnaka Bay on the island of Cyprus, occupies a special position in the discussions about the collapse of Late Bronze Age societies around 1200 BCE, the Crisis Years, and the potential role of the “Sea Peoples” mentioned in Egyptian and Near Eastern sources in this collapse. The successive excavation campaigns that have taken place on the hill thus far have revealed the remains of a short-lived, well-organised settlement with an abundant material culture that testifies to relations with several regions of the Mediterranean.